Modulation of the granzyme B inhibitor proteinase inhibitor 9 (PI-9) by activation of lymphocytes and monocytes in vitro and by Epstein–Barr virus and bacterial infection - Classen, C F (Blackwell Science Inc, 2006)
Proteinase inhibitor 9 (PI-9) is an intracellular serpin expressed in lymphocytes and monocyte-derived cells. It is the only known endogenous natural antagonist of granzyme B (GrB), and its proposed function is protection of cells from misdirected GrB. We have studied the regulation of PI-9 in primary peripheral blood mononuclear cells (PBMCs) following ex-vivo stimulation, and in PBMCs from patients suffering from viral or bacterial infections. By intracellular flow cytometry, we found identical PI-9 expression in all lymphocyte subsets, lower levels in monocytes and none in granulocytes. PI-9 was stable for 48 h in the presence of cycloheximide, indicating slow protein turnover. Incubation of PBMCs with several stimuli including lipopolysaccharide (LPS) led to up-regulation in the monocyte, but not the lymphocyte fraction, within 48 h, inhibitable by the NF-κB inhibitor pyrrolidin dithiocarbamate (PTDC). Up-regulation of PI-9 was observed in lymphocytes and monocytes of patients with acute Epstein–Barr virus (EBV), but not bacterial infection. Preterm infants had similar PI-9 expression as adults in monocytes, but lower in lymphocytes, decreasing during bacterial infection. Taken together, our data indicate that PI-9 is rapidly up-regulated upon stimulation of monocytes, but not lymphocytes. By protecting monocytes and macrophages from misdirected GrB in the inflammatory process, PI-9 might be involved in the regulation of antigen presentation.